Devices for quality control of welded joints of leads of packageless chips - Spirin, V. G. (Technology and design in electronic equipment, 2013)
The author considers the design and operation of two devices for quality control of welded joints between aluminium leads of packageless microcircuits and contact pads of a thin-film circuit.